2014
DOI: 10.3390/molecules19056754
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Route to Tailoring Peptide-Stabilized Gold Nanoparticles Using Glutathione as a Synthon

Abstract: Abstract:The preparation of gold nanoparticles (AuNPs) of high purity and stability remains a major challenge for biological applications. This paper reports a simple synthetic strategy to prepare water-soluble peptide-stabilized AuNPs. Reduced glutathione, a natural tripeptide, was used as a synthon for the growth of two peptide chains directly on the AuNP surface. Both nonpolar (tryptophan and methionine) and polar basic (histidine and dansylated arginine) amino acids were conjugated to the GSH-capped AuNPs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…The CdS quantum dots were previously characterized in deionized water and seawater; it was observed that the majority of CdS quantum dots kept their nanoscale dimensions (3-10 nm) in all media tested [12]. The behavior of polypeptide-stabilized NPs is complex, and, depending on the combination of amino acids present, the stability of the resulting particles to aggregation can be very variable, as evidenced recently by Ho Wu et al [29]. However, the CdS quantum dots used in the present study were stabilized by the tripeptide glutathione, which may provide stability in neutral pH saline media by a mechanism derived from the electrostatic repulsion between negatively charged carboxylic groups in the forms of zwitterions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The CdS quantum dots were previously characterized in deionized water and seawater; it was observed that the majority of CdS quantum dots kept their nanoscale dimensions (3-10 nm) in all media tested [12]. The behavior of polypeptide-stabilized NPs is complex, and, depending on the combination of amino acids present, the stability of the resulting particles to aggregation can be very variable, as evidenced recently by Ho Wu et al [29]. However, the CdS quantum dots used in the present study were stabilized by the tripeptide glutathione, which may provide stability in neutral pH saline media by a mechanism derived from the electrostatic repulsion between negatively charged carboxylic groups in the forms of zwitterions.…”
Section: Discussionmentioning
confidence: 76%
“…However, the CdS quantum dots used in the present study were stabilized by the tripeptide glutathione, which may provide stability in neutral pH saline media by a mechanism derived from the electrostatic repulsion between negatively charged carboxylic groups in the forms of zwitterions. The behavior of polypeptide-stabilized NPs is complex, and, depending on the combination of amino acids present, the stability of the resulting particles to aggregation can be very variable, as evidenced recently by Ho Wu et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although close nanoparticle-nanoparticle interactions are found in solution, the UV-Vis absorbance spectrum of the conjugated Au-GSH NPs showed a surface plasmon resonance (SPR) at λ max at 522 nm ( Figure S2e ) indicating no significant red-shift of the SPR band resulting from aggregation of the materials after surface conjugation of terminal amino acids and purification. Similarly, no significant change in the diameter, hydrodynamic radius, and SPR band of the Au-GSH-(X) 2 -U3 was observed after multiple purification steps ( Figure S3 ) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is possible that there is less GSH on the surface than estimated and that Trp is coupling to the amine of GSH to form a GSH-(X) 3 species. While we were not able to confirm the ligand structure of Au-GSH-X 2 -U2 NPs, we were able to confirm the composition of the ligand structure of Au-GSH-X 2 -U3 NPs by 1 H NMR spectroscopy [ 21 ]. Cyanide and HCl etched samples of Au-GSH-X 2 -U3 in methanol showed the presence of only free GSH-X 2 in samples prepared by U3 ligands [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation